2010
DOI: 10.1177/0020872810372368
|View full text |Cite
|
Sign up to set email alerts
|

Age discrimination in the labour market from the perspectives of employers and older workers

Abstract: This article presents the findings of a study on age discrimination against older workers in Hong Kong. The study collected survey data from 787 older workers aged 45 or above and 283 employers who were managers responsible for personnel or human resources management, or for hiring people for organizations. The focus is on revealing the influences of the organizational goals of profit-making and social responsibility on age discrimination, along with influences from negative stereotyping and other factors. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…Numerous researches have been published as the numbers of information quickly rises, on the relationship between age and numerous magnitudes of studies includes age discrimination [2,4,5,24,[36][37][38], age stereotypes [37,39,40] and age-related psychological factors [38,[41][42][43] as well as the employability of older employees in the organizations [26,[44][45][46][47]. In the USA, Popkin et al [48] reviewed on the impacts of an aging workforce in transportation sector by adopting the sociotechnical systems model.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous researches have been published as the numbers of information quickly rises, on the relationship between age and numerous magnitudes of studies includes age discrimination [2,4,5,24,[36][37][38], age stereotypes [37,39,40] and age-related psychological factors [38,[41][42][43] as well as the employability of older employees in the organizations [26,[44][45][46][47]. In the USA, Popkin et al [48] reviewed on the impacts of an aging workforce in transportation sector by adopting the sociotechnical systems model.…”
Section: Methodsmentioning
confidence: 99%
“…The evidence from European social surveys carried out in the first year after the economic crisis of 2008 (European Commission 2009) showed a strong conviction that the economic crisis would negatively influence the position of older workers in job markets through the increase in age discrimination. Analysis from the point of view of employers and companies also revealed that in a situation of economic slowdown and deterioration of market opportunities, the burden shifted towards older employees by cutting their salaries (which are sometimes higher due to seniority schemes) or by making them redundant (Cheung et al 2010). The research evidence from recent years, however, shows that while younger people in many EU countries have faced severe difficulties in finding jobs since the crisis of 2008, employment rates of prime-age and older workers have remained remarkably stable (Eichhorst et al 2013).…”
Section: Globalisation and Economic Crisesmentioning
confidence: 99%
“…Legislation is not always able to address this type of age discrimination (Cheung et al 2010), where social factors, such as stereotypes, interpersonal relationships or work atmosphere can play a significant role. This suggests that the discrimination in employment might occur in two forms: one that aligns with the strict legal definitions, and second form that occurs in social interactions and is linked to workplace dynamics (Green 2001).…”
Section: Legal and Social Understanding Of Age Discriminationmentioning
confidence: 99%